ANALISIS KUALITAS PELAYANAN DI MALL PELAYANAN PUBLIK KOTA CIMAHI: PENDEKATAN KUALITATIF DESKRIPTIF - Syeima Annisa Putri (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2025)
Public service is a key pillar of bureaucratic reform in Indonesia, and the Public Service Mall (MPP) is a strategic innovation for delivering integrated, fast, and efficient services. This study uses a descriptive qualitative approach to analyze service quality at the Cimahi City MPP based on five SERVQUAL dimensions: tangible, reliability, responsiveness, assurance, and empathy. Data were collected through observation, in-depth interviews, and documentation with informants from employees, managers, and service users. Data were then analyzed using the Miles, Huberman, and Saldaña model. The results indicate that the tangible and assurance dimensions have performed well, reflecting modern facilities and professional attitudes of officers. However, the reliability, responsiveness, and empathy dimensions still face challenges such as delays in cross-agency services, suboptimal coordination, and variations in empathetic attitudes among officers. This study concludes that the Cimahi City MPP has become a positive example of public service innovation, but strengthening inter-agency coordination, service digitization, and excellent service training are needed to achieve optimal service quality